Endoparasites of two species of forage fish from the Três Marias reservoir, Brazil: new host records and ecological índices - de Albuquerque, Marcia Cavalcanti; Clapp, Michelle Daniele dos Santos; Sato, Marilia de Carvalho Brasil (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. de Albuquerque M.C., dos Santos-Clapp M.D. & Brasil-Sato M. de C. Endoparasites of two species of forage fish from the Três Marias reservoir, Brazil: new host records and ecological índices. [Endoparasitos de duas espécies de peixes forrageiros do reservatório de Três Marias, Brasil: novos registros de hospedeiros e seus índices ecológicos.] Revista Brasileira de Medicina Veterinária, 38(supl. 3):139-145, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, km 7, Campus Seropédica, RJ, Brasil, 23897-970. E-mail: marciabiologia@hotmail.com Tetragonopterus chalceus and Triportheus guentheri are important forage fish from the Três Marias reservoir, which is located on the upper São Francisco river, State of Minas Gerais, Brazil. Here, their endoparasitic fauna was investigated for the first time. These two fish species have similar diets, despite different foraging strategies. This similarity is reflected in the findings regarding their parasite communities, which indicate overlapping of niches between these species. The qualitative similarity between the two parasite communities was evident (Jaccard index = 0.78), however the quantitative similarity was slight (Sorenson index = 0.28). The community of T. chalceus was richer but less diverse (13 species; H´ = 0.43) than that of T. guentheri (12 species; H´ = 0.86). Both fish species were found to be parasitized by plerocercoids of Proteocephalidea (Eucestoda); larvae of Contracaecum sp., Hysterothylacium sp., Goezia sp., Procamallanus (Spirocamallanus) sp., Spiroxys sp., Rhabdochona sp. and Cystidicoloides fischeri; adult specimens of Procamallanus (Spirocamallanus) saofranciscencis (Nematoda); spores of Henneguya sp. (Myxozoa); and oocysts of Calyptospora sp. (Apicomplexa). In addition to these, Creptotrema creptotrema (Digenea) and Spinitectus rodolphiheringi (Nematoda) were also present in T. chalceus; and larvae of Procamallanus (Spirocamallanus) sp. (Nematoda) were found in T. guentheri. Procamallanus saofranciscencis and plerocercoids of Proteocephalidea were the parasites with highest prevalence and highest mean abundance, respectively, in the community of T. chalceus. Larvae of Rhabdochona sp. had the highest prevalence and mean abundance in the parasite community of T. guentheri. Tetragonopterus chalceus and T. guentheri constituted new hosts for plerocercoids of Proteocephalidea, larvae of the nematodes Goezia sp., Spiroxys sp. and C. fischeri and spores of Henneguya sp.; T. chalceus was a new host for S. rodolphiheringi; and T. guentheri was a new host for larvae of Hysterothylacium sp.